2016
DOI: 10.1590/1678-457x.05616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different periods of pre-slaughter stress on the quality of the Nile tilapia meat

Abstract: The study was carried out with the objective of evaluating the influence of pre-slaughter stress on meat quality of Nile tilapia (O. niloticus) for 10 days of storage in ice. 75 whole fish were used eviscerated, with average weight and length of 825.75 ± 101.59 g and 28.25 ± 0.81 cm, respectively. The treatments consisted of time in which the animals underwent pre-slaughter hypoxia, being 0, 3 and 6 minutes. Rigor mortis and muscle pH were assessed besides the application of the Quality Index Method and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Almeida et al (2006) observed pH between 6.07 and 6.66 in farmed tambaquis kept in ice for 43 days, with a small variation in the first days of storage and a significant increase after 19 days. Similar results were also observed by Concollato et al (2016) and Castro et al (2016). The increase in pH is likely related to the accumulation of basic substances such as ammonia and trimethylamine, which are produced by microorganism development in fish (Huss, 1998).…”
Section: Discussionsupporting
confidence: 67%
“…Almeida et al (2006) observed pH between 6.07 and 6.66 in farmed tambaquis kept in ice for 43 days, with a small variation in the first days of storage and a significant increase after 19 days. Similar results were also observed by Concollato et al (2016) and Castro et al (2016). The increase in pH is likely related to the accumulation of basic substances such as ammonia and trimethylamine, which are produced by microorganism development in fish (Huss, 1998).…”
Section: Discussionsupporting
confidence: 67%
“…Fishes were kept out of water under anoxia for different periods; these included 0 min (slaughtered immediately after being taken out of the tank) and 3 and 6 min of anoxia to simulate acute ante-mortem stress, which are common in fish farming. This method followed the recommendations of Davis & Schreck (1997), Martins et al (2004) and Castro et al (2017).…”
Section: Experimental Designmentioning
confidence: 99%
“…Em geral, o consumo de pescados é mediado por parâmetros avaliados pelo consumidor no ato da compra como tamanho, coloração do corpo, espécie, tipo de revestimento corporal, além do odor, cor dos olhos, firmeza do corpo e das brânquias, isto no caso dos peixes não processados (Castro et al, 2017). Por outro lado, tem ocorrido uma mudança de comportamento entre os consumidores no consumo de outras formas de preparo do pescado, divido a uma series de fatores socioculturais, como o consumo de peixe cru, ligeiramente cozido ou condimentado em pratos da culinária hispano-americana como o "ceviche" e, principalmente, a japonesa com os pratos mais tradicionais, "sushi" e "sashimi" (Perez et al, 2004).…”
Section: Resultados E Discussõesunclassified